Analisis Kepemimpinan dan Proses Organisasi di Perguruan Tinggi (Kasus di Fakultas Ilmu Administrasi Universitas 17 Agustus 1945 Jakarta) - Agus Sjafari (Universitas Sultan Ageng Tirtayasa, 2013)
College as an educational institution is an organization that is very close to the community, its existence is determined by acceptance. The choice of the Faculty of Administrative Sciences August 17, 1945 Jakarta (Jakarta UTA'17) based on the assumption that the organization is within the scope of UTA'17 Jakarta that have characteristics that differentiate with other faculty. Based on the discussion, there are some conclusions of this research are: 1) The leadership shown by the leadership in the Faculty of Administrative Sciences Jakarta August 17, 1945 are included in the category of Being a tendency to good categories, and 2) Variable organizational processes displayed by the leadership Faculty of Administration at the University of Jakarta August 17, 1945 included in the category of Being a tendency to lead to bad category.